Adsorption of diclofenac sodium from aqueous solution using Fe-Mn binary oxides parametric, optimization, isotherm and kinetics study - Ensano, Benny Marie B. (2013)
Diclofenac (DCF), is a widelyused non-steroidal anti-inflammatory drug, has been detected in effluents of conventional wastewater treatment palnts worldwide. The presence of this compound in varouos water resources even at very low concentrations poses a big threat both to human and aquatic ecosystems. The aim of this study is to investigate the removal of diclofenac from aqueous solution using Fe-Mn binary oxides (FMBO) as alternative adsorbents. Synthetic FMBO with varying Fe/Mn molar ratio of 1:0, 3:1 and 1:1 were prepared through simultaneous oxidation and co-precipitation methods. Batch experiments were conducted to evaluate the effects of operating parameters namely, FMBO dosage, initial diclofenac concentration, Fe/Mn molar ratio, contact time and initial pH on diclofenac removal. FMBO gave the highest diclofenac removals of 99%, 98% and 96% at pH 3, 5, and 7 for 1:1, 3:1 and 1:0 FMBO, respectively. In addition, diclofenac removals improved with a decrease in Fe/Mn molar ratio and increase in FMBO dosage, contact time and initial diclofenac concentration. Optimization for 3:1 FMBO using Box-Behnken Design resulted in up to 28 mg/g diclofenac removal at optimal operating conditiond (pH 7, 100 ppm initial diclofenac concentration and 50 mg FMBO adsorbent dose). Freundlich isotherm (R² = 0.9854) and Pseudo-second-order kinetic model (R² = 0.9972) best described experimental data indicating that the adsorption process is heterogeneous and chemisorption in nature.